2015
DOI: 10.1002/ajpa.22732
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma: Methods for the identification of physeal fractures in nonadult skeletal remains

Abstract: This study highlights the potential for recognizing physeal fractures in children of all ages, enhancing our understanding of nonadult trauma, and enabling us to assign a more precise age of the injury to build up a picture of their activities in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This impedes differentiation between some accidental and intentional traumas as they may both result in similar fracture types; for example, ulnar diaphyseal fractures may be produced during an accidental fall, or by a blow (i.e., parry fracture) (Judd 2008;Judd and Redfern 2012). Finally, barring the application of destructive analyses (e.g., Boer et al 2012) or indirect inference of age from fractures sustained at particular developmental stages (Duchesneau and Fallat 1996;Lovejoy and Heiple 1981;Verlinden and Lewis 2015), it is typically not possible to determine the age at which many healed fractures were sustained, or in the case of multiple fractures, if the injuries occurred simultaneously or resulted from multiple events.…”
Section: Fracture Recording and Radiographymentioning
confidence: 99%
“…This impedes differentiation between some accidental and intentional traumas as they may both result in similar fracture types; for example, ulnar diaphyseal fractures may be produced during an accidental fall, or by a blow (i.e., parry fracture) (Judd 2008;Judd and Redfern 2012). Finally, barring the application of destructive analyses (e.g., Boer et al 2012) or indirect inference of age from fractures sustained at particular developmental stages (Duchesneau and Fallat 1996;Lovejoy and Heiple 1981;Verlinden and Lewis 2015), it is typically not possible to determine the age at which many healed fractures were sustained, or in the case of multiple fractures, if the injuries occurred simultaneously or resulted from multiple events.…”
Section: Fracture Recording and Radiographymentioning
confidence: 99%
“…Two cases of trauma were found in the subadult assemblage (4.7%). The first case was a 2‐ to 3‐year‐old with a moderate ante mortem fracture on distal epiphysis of the right radius that was mostly healed by the time of death and likely resulted in joint misalignment or angulation (Verlinden & Lewis, ) (Figure ). This was the only skeletal element of the individual's arm, making direct observation of the elbow joint impossible.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a healed disarticulation of either the radius or ulna; however, neither bone was recovered from the site, so additional observation is impossible. Verlinden & Lewis () note that in modern children, epiphysial fractures in the elbow joint are usually associated with accidental falls, suggesting that these injuries were likely unintentional in nature, possibly due to accidental fall while learning to walk. This may be an additional risk factor for subadults 1.5–3 years old who are becoming increasingly mobile and placed at risk for accidental trauma and exposure to dangerous elements.…”
Section: Resultsmentioning
confidence: 99%
“…Although not carried out in a deceased population, the study of Liversidge et al (2010) has important implications for the dental aging methods employed in paleopathological contexts and is therefore included in this review: using panorex radiographs from 946 living children 3-16 years old, they assessed four dental maturity scales and 15 aging methods based on individual teeth. The remaining two studies with 500+ individuals used radiographs to assess findings identified first on macroscopic examination (Brickley et al, 2018;Verlinden & Lewis, 2015). Individuals evaluated ranged in age from fetal to 19 years (for examples of the range, see Adams et al, 2019;Beyer-Olsen & Risnes, 1994;Brickley et al, 2018;Cowgill, 2007;Gaither, 2012;Geber, 2014;Newman et al, 2019;Newman & Gowland, 2017).…”
Section: Overview and Descriptive Statisticsmentioning
confidence: 99%